2006
DOI: 10.1200/jco.2004.00.1792
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Cetuximab, Cisplatin, and Concomitant Boost Radiotherapy for Locoregionally Advanced, Squamous Cell Head and Neck Cancer: A Pilot Phase II Study of a New Combined-Modality Paradigm

Abstract: This regimen is not currently recommended outside of the clinical trial setting. Further investigation of its safety profile is needed. However, preliminary efficacy is encouraging, and further development of this targeted combined-modality paradigm is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
1
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(188 citation statements)
references
References 32 publications
5
171
1
11
Order By: Relevance
“…In contrast, the optimisation of the cisplatin -irinotecan -radiotherapy regimen could be potentially feasible. Epidermal growth factor receptor (EGFr) antibody or inhibitor could also increase the efficacy of the regimen: first by improving the therapeutic effect of irinotecan via EGFr antibodies as demonstrated in vitro (Prewett et al, 2002), second by the specific approach as demonstrated in head and neck cancer, by using radiation therapy and EGF receptor antibodies (Bonner et al, 2006;Pfister et al, 2006). The association cisplatinirinotecan -radiotherapy with EGFr antibody warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the optimisation of the cisplatin -irinotecan -radiotherapy regimen could be potentially feasible. Epidermal growth factor receptor (EGFr) antibody or inhibitor could also increase the efficacy of the regimen: first by improving the therapeutic effect of irinotecan via EGFr antibodies as demonstrated in vitro (Prewett et al, 2002), second by the specific approach as demonstrated in head and neck cancer, by using radiation therapy and EGF receptor antibodies (Bonner et al, 2006;Pfister et al, 2006). The association cisplatinirinotecan -radiotherapy with EGFr antibody warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot phase II study of concurrent cetuximab, cisplatin and concomitant boost radiotherapy for locoregionally advanced SCCHN patients (n ¼ 32) reported a 3-year OS of 75%, PFS of 56% and a locoregional control rate of 71%. However, the study was closed for significant AEs including two deaths (Pfister et al, 2006). A randomised phase III study compared radiation with or without cetuximab for patients with locally advanced inoperable SCCHN patients (Bonner et al, 2006).…”
Section: Anti-egfr Mabsmentioning
confidence: 99%
“…Early phase studies of EGFRIs given concurrently with RT/platinum have demonstrated feasibility and an attendant increase in both expected and unexpected toxicities [45]. A single-arm phase II study of RT/cisplatin/ cetuximab, for example, demonstrated encouraging 3-year OS of 76% and 3-year PFS of 56%, but rates of adverse events (AEs) including myocardial infarction were unacceptably high [46]. When studied in a prospective comparative fashion, as occurred in the RTOG 0522 study, the addition of cetuximab to RT/cisplatin increased toxicity without improving PFS or OS [27].…”
Section: Definitive Therapy For Unresectable Diseasementioning
confidence: 99%